Risk for Gestational Diabetes Mellitus and Adverse Birth Outcomes in Chinese Women with Polycystic Ovary Syndrome - Qing Xiao; Yong-Yi Cui; Jine Lu; Guo-Zheng Zhang; Fang-Ling Zeng (International Journal of Endocrinology)
Objective. To examine the association of polycystic ovary syndrome (PCOS) in early pregnancy with gestational diabetes mellitus (GDM) and adverse birth outcomes. Methods. In this retrospective cohort study including 2389 pregnant women, the medical records of 352 women diagnosed with PCOS were evaluated. Outcomes included GDM, preterm birth, low birth weight, macrosomia, and being small and large for gestational age. Multivariable logistic regression models were used to examine the association of the risk for GDM and adverse birth outcomes with PCOS after adjusting for confounders. Results. Women previously diagnosed with PCOS had a higher risk of GDM (adjusted odds ratio [OR] 1.55, 95% confidence interval [CI]: 1.14–2.09). A strong association was seen between PCOS and preterm birth (adjusted OR 1.69, 95% CI: 1.08–2.67). On stratified analysis, the adjusted OR for GDM among women with PCOS undergoing assisted reproductive technology was 1.44 (95% CI: 1.03–1.92) and among women with PCOS who conceived spontaneously was 1.60 (1.18–2.15). No increased risk for other adverse birth outcomes was observed. Conclusions. Women with PCOS were more likely to experience GDM and preterm birth.